Coworking as the great good place for design learning. An exploratory framework - Mendes, Fernando E. (2019)
Abstract : In this paper we explore a conceptual framework based on three lines of thinking/work from Patrick Cohendet (Underground/Middleground/Upperground), Ray Oldenburg (The Great Good Place), and Fred Garneti (Heutagogy or Self-determined Learning). To demonstrate the relevance and feasibility of our proposed concept, we review the key factors and definitions of these authors and their work. Although not a theoretical framework, the present paper aims to help us map a part of our research work within the context of the Doctoral Programme in Design at IADE / Universidade Europeia, which triangulates Coworking, Design Learning, and Heutagogy or selfdetermined modes of learning. Ultimately, the aim is to generate new evidence on how such a model of Coworking Design Learning can benefit and betier suit contemporary Design learners.